Charge! EVs power up for the long haul. - Toepfer, C.B (IEEE spectrum)
By making standardized charging stations as common and as safe as gas stations, the electric-vehicle industry hopes to drive itself into transportation's mainstream. Consumer safety was of the essence. Thus, the top priority requirements of a standard EV charging system and associated ?plug? were that it first and foremost be not only safe, but perceived as safe; that it be intuitive and easy for consumers to use; and that it be cost-effective. Ideally, too, a standard charge coupler between the vehicle and power source would be compatible with electric networks around the world. These issues are discussed as are inductive and conductive charging options